2021
DOI: 10.1302/2046-3758.104.bjr-2020-0085.r2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products induce inflammatory responses and invasive behaviour in fibroblast-like synoviocytes via the RAGE-NF-κB pathway

Abstract: Aims Rheumatoid arthritis (RA), which mainly results from fibroblast-like synoviocyte (FLS) dysfunction, is related to oxidative stress. Advanced oxidation protein products (AOPPs), which are proinflammatory mediators and a novel biomarker of oxidative stress, have been observed to accumulate significantly in the serum of RA patients. Here, we present the first investigation of the effects of AOPPs on RA-FLSs and the signalling pathway involved in AOPP-induced inflammatory responses and invasive behaviour. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…20 Loss of normal synovial protection alters the proteinbinding characteristics of the cartilage surface, promoting adhesion and invasion by fibroblast-like synoviocytes (FLSs), and the proliferation of FLSs is the main cause of invasive pannus formation in RA pathogenesis. 21,22 FLSs synthesize matrix metalloproteinases (MMPs), particularly MMP-1, -3, -8, -13, -14, and -16, promoting breakdown of the type II collagen network, a process that alters glycosaminoglycan content and water retention, directly leading to biomechanical dysfunction. 23 A recent study found that overexpressed microRNA (miR)-486 accelerates the reduction of aggregative proteoglycan by upregulating the expression of A disintegrin and metalloproteinase with thrombospondin motifs-4 (ADAMTS4) and MMP-13, resulting in more decomposition of chondrocytes.…”
Section: Ra Pathogenesismentioning
confidence: 99%
“…20 Loss of normal synovial protection alters the proteinbinding characteristics of the cartilage surface, promoting adhesion and invasion by fibroblast-like synoviocytes (FLSs), and the proliferation of FLSs is the main cause of invasive pannus formation in RA pathogenesis. 21,22 FLSs synthesize matrix metalloproteinases (MMPs), particularly MMP-1, -3, -8, -13, -14, and -16, promoting breakdown of the type II collagen network, a process that alters glycosaminoglycan content and water retention, directly leading to biomechanical dysfunction. 23 A recent study found that overexpressed microRNA (miR)-486 accelerates the reduction of aggregative proteoglycan by upregulating the expression of A disintegrin and metalloproteinase with thrombospondin motifs-4 (ADAMTS4) and MMP-13, resulting in more decomposition of chondrocytes.…”
Section: Ra Pathogenesismentioning
confidence: 99%
“…AOPPs resulting from myeloperoxidase activation and hypochlorous acid production during inflammation are capable of binding to pattern recognition receptors (PRRs) whose downstream effects result in the activation of OS and inflammatory pathways including nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and nuclear factor-κB (NF-κB) activation [ 30 ]. Among the PPRs activated by AOPPs, the receptor of advanced glycation end-products (RAGE) is implicated in diverse chronic inflammatory states and has been linked to vascular lesions in diabetes, renal diseases, and atherosclerosis [ 31 , 32 ]; AOPPs have been also found increased in patients with inflammatory conditions such as Crohn’s disease [ 4 ], rheumatoid arthritis [ 33 ], and obstructive sleep apnea syndrome [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…After 24 hours, the cells were fixed with 4% paraformaldehyde. 34 Cells were permeabilized with 0.1% Triton in PBS, blocked with QuickBlock (P0260, Shanghai, China, Beyotime) blocking buffer, and incubated with primary antibodies against aggrecan (1:500, Abcam, USA, Cat. No.…”
Section: Methodsmentioning
confidence: 99%